Accounting Betas, Systematic Operating Risk, and Financial Leverage: A Risk-Composition Approach to the Determinants of Systematic Risk - Hill, Ned C.; Stone, Bernell K. (Journal of Financial and Quantitative Analysis, 1980)
Ned C. Hill, Bernell K. Stone, Accounting Betas, Systematic Operating Risk, and Financial Leverage: A Risk-Composition Approach to the Determinants of Systematic Risk, The Journal of Financial and Quantitative Analysis, Vol. 15, No. 3 (Sep., 1980), pp. 595-637